Transfemoral valve‐in‐valve implantation for degenerated bioprosthetic aortic valves using the new balloon‐expandable Edwards Sapien 3 valve. Issue 4 (3rd May 2016) - Gonska, Birgid; Seeger, Julia; Rodewald, Christoph; Scharnbeck, Dominik; Rottbauer, Wolfgang; Wöhrle, Jochen
Abstract : Background: Surgical aortic bioprosthetic valves deteriorate 10 to 20 years after operation. Valve‐in‐valve implantation with first generation transcatheter aortic valve implantation (TAVI) devices has shown to be feasible. We report a first case series with the new Edwards Sapien 3 valve for transfemoral aortic valve‐in‐valve implantation. Methods and results: Nine patients underwent valve‐in‐valve‐TAVI with the Edward Sapien 3 valve. Seven patients presented with severe aortic stenosis and two patients with severe aortic insufficiency of surgical aortic bioprosthesis. Procedures were performed in local anaesthesia under fluoroscopic guidance with pre‐procedural 256 multislice computed tomography for procedural planning. In all patients the Edwards Sapien 3 was successfully implanted decreasing the mean echocardiographic gradient from 42 ± 22mmHg to 18 ± 7mmHg (p < 0.01). Device success according to VARC 2 criteria was achieved in 8 out of 9 patients. There was no death, coronary obstruction, use of second valve or need for post‐dilation. Furthermore there were no access‐site complications, no minor or major bleedings or vascular injury. Two patients required pacemaker implantation within the first 7 days after valve‐in‐valve TAVI. Post‐procedural echocardiography demonstrated no or trace aortic regurgitation. Early safety events within 30 days according to VARC‐2 definition occurred in 1 patient. Conclusions: The Edwards Sapien 3 valve for treatment of failed surgical bioprostheses is feasible and is associated with no relevant post‐procedural aortic regurgitation and a low risk of access site complications. © 2016 Wiley Periodicals, Inc.